2022
DOI: 10.1093/cdn/nzab152
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Effects of a Family-Based Childhood Weight-Management Intervention on Parental Nutrient Biomarkers and Cardiometabolic Risk Factors

Abstract: Background Parental involvement has been shown to favorably affect childhood weight management interventions, but whether these interventions influence parental diet and cardiometabolic health outcomes is unclear. Objective To evaluate whether a 1-year family-based childhood weight management intervention altered parental nutrient biomarker concentrations and cardiometabolic risk factors (CMRF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Consistent with the broad anti-inflammatory effects of C15:0 shown in our current study, daily oral C15:0 supplementation over 12 weeks lowers the proinflammatory cytokines MCP-1, IL-6, and TNFα, as well as IgG, in animal models of metabolic and liver disease [2]. These effects are aligned with inverse associations found between circulating inflammatory markers (i.e., C-reactive protein and adipokines) and C15:0 in humans [30,31,95]. On the lipid front, daily oral C15:0 supplementation for 12 weeks lowers total cholesterol and triglycerides in animal models of metabolic syndrome and nonalcoholic steatohepatitis [2].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with the broad anti-inflammatory effects of C15:0 shown in our current study, daily oral C15:0 supplementation over 12 weeks lowers the proinflammatory cytokines MCP-1, IL-6, and TNFα, as well as IgG, in animal models of metabolic and liver disease [2]. These effects are aligned with inverse associations found between circulating inflammatory markers (i.e., C-reactive protein and adipokines) and C15:0 in humans [30,31,95]. On the lipid front, daily oral C15:0 supplementation for 12 weeks lowers total cholesterol and triglycerides in animal models of metabolic syndrome and nonalcoholic steatohepatitis [2].…”
Section: Discussionsupporting
confidence: 89%
“…These mechanisms are aligned with the demonstrated anti-inflammatory, antifibrotic, and anticancer activities of C15:0 in vitro and in vivo [2,[25][26][27][28]. They are also consistent with epidemiological studies linking higher circulating C15:0 concentrations to lower cholesterol, triglycerides, ApoA1 and ApoB, liver enzymes, C-reactive protein, adipokines, body mass index; and improved insulin sensitivity and β cell function in humans [29][30][31][32][33][34].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous work has shown that addressing health conditions in children has an outsized impact on behavior changes for the entire family, suggesting that there may be opportunities to promote increased engagement when the entire household is included in the intervention. 94–96…”
Section: Outstanding Questions and Gaps In The Fieldmentioning
confidence: 99%
“…Previous work has shown that addressing health conditions in children has an outsized impact on behavior changes for the entire family, suggesting that there may be opportunities to promote increased engagement when the entire household is included in the intervention. [94][95][96] A crucial comparative effectiveness question (which also affects intervention cost and cost-effectiveness) is the optimal duration of intervention. An important area remains understudied: If FIM interventions are time limited, what happens when they end?…”
Section: Comparative Effectivenessmentioning
confidence: 99%